Anterior Minimally Invasive Plate Osteosynthesis for Humeral Shaft Fractures Is Safer Than Open Reduction Internal Fixation: A Matched Case-Controlled Comparison. Issue 8 (August 2021) - Randell, Matthew; Glatt, Vaida; Stabler, Annabelle; Bussoletti, Timothy; Hohmann, Erik; Tetsworth, Kevin
Abstract : Objective: Compare anterior minimally invasive plate osteosynthesis (MIPO) to open reduction/internal fixation (ORIF) for humeral shaft fractures, assessing complications and clinical outcomes. Design: Retrospective matched case-controlled cohort. Setting: Tertiary referral trauma centre. Patients/Participants: Humeral shaft fractures identified retrospectively over 5 years; 31 were treated by MIPO and 54 by ORIF. Matched-case cohort assembled according to fracture pattern, sex, age, and comorbidities, with 56 total patients (28 per group). Interventions: MIPO and ORIF. Main Outcome Measures: Complication rate was the primary outcome (radial nerve injury, nonunion, infection, and reoperation). Radiographic alignment and the Disabilities of the Arm, Shoulder and Hand Score were secondary outcomes. Results: Cumulative complication rates were 3.6% after anterior MIPO and 35.7% after ORIF ( P = 0.0004). The only complication after anterior MIPO was a nonunion, managed with revision ORIF and bone graft. The ORIF group had 10 complications, including 5 superficial infections, 4 iatrogenic radial nerve injuries, and 1 nonunion. The mean Disabilities of the Arm, Shoulder and Hand score after MIPO was 17.0 ± 18.0 and after ORIF was 24.9 ± 19.5. The mean coronal plane angulation after MIPO was 1.8 ± 1.3 degrees and after ORIF was 1.0 ± 1.2 degrees. The mean sagittal plane angulation after MIPO was 3.0 ± 2.9 degrees and after ORIF was 1.0 ± 1.2 degrees. Conclusions: The cumulative complication rate was 10 times higher after ORIF of humeral shaft fractures compared with the MIPO technique. MIPO achieved nearly equivalent radiographic alignment, with no clinically meaningful differences observed. MIPO is the safer option and should be considered for patients with humeral shaft fractures that would benefit from surgical intervention. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.